Analysis of Risk Factors for Obesity in Urban Children in Some Elementary School in Jember Regency - Jasmine Fachrunnisa; Cholis Abrori; Dwita Aryadina Rachmawati (Journal of Agromedicine and Medical Sciences, 2016)
The prevalence of obesity in children has steadily increased, not only in the world but also in Indonesia. Urban area as a central of economic led the higher prevalence of childhood obesity than in rural areas. The objective of this study was to analyze the risk factors associated with obesity among urban elementary school childrens in Jember. A cross sectional study was conducted with a total sample of 176 pupils. Anthropometric status determined using body mass index for age and obesity stated if z-score exceed >+2SD based on WHO 2007. The questionnaire about risk factors was filled with interview. Analysis data performed with univariate, bivarate, and multivariate analysis. This study showed the prevalence of obesity was 17%. Overall, our result showed that in non modifiable risk factors, the prevalence of obesity was significantly higher in children who had obese parent when compared to children who hadn't. Children who had obese parent had the more risk of obesity by 6 times. In modifiable risk factors, children who had meal more than 3 times per day had the more risk of obesity by 2 times. Drinking milk frequently according to Dietary Guideline for American 2015 has a protective factors against obesity.Keywords: childhood obesity, urban, risk factor